Impacts of different fencing periods and grazing intensities on insect diversity in the desert steppe in Inner Mongolia - Wang, Ning; Song, Xiaoxiao; Wang, Jiayu; Wang, Liming (Frontiers in Ecology and Evolution, 2022)
Grassland insect diversity plays an important role in the maintenance of plant species and functional diversity. Degradation and desertification of the Inner Mongolian grasslands in China is a major socioeconomic and environmental challenge that has been driven predominantly by livestock overgrazing. To understand how livestock grazing influences insect diversity, we sampled six plots with different fencing periods (3 or 7 years) and grazing intensities (0, 6, or 12 sheep per ha). Dominant groups in the grassland insect community were Hemiptera and Orthoptera. Ungrazed plots that were fenced for 3 years showed the highest species diversity and richness values. Our results suggest that policies that remove livestock from the desert grassland for long periods (7+ years) are not beneficial for maintaining insect diversity, and we recommend the most suitable grazing intensity for the sustainability of biodiversity of the desert steppe in Inner Mongolia is light grazing (8 sheep/ha 0.5 yr-1), and the most suitable fencing period is three years. Thus, periodic livestock grazing is important in the design of management actions to preserve biodiversity.